Integrando a sustentabilidade à cadeia de suprimento da madeira: uma análise das práticas de sustentabilidade dos membros da cadeia de madeira localizadas no Oeste do Paraná - Possamai, Victor Yuri (2023)
Given the evidence involving the constant search for efficiency in the various supply chains, sustainability is a fundamental element in the production model of the new century. Through this theme, it should be noted that the timber sector is highly representative of the global economy, given the versatility and diversity of options for using this resource; even so, there is a constant intensity in movements led by governments, industries, and society in general concerning the global need to adhere to environmental preservation practices to guarantee the permanence and survival of natural resources. The study analyzes which sustainability practices have been adopted by members of the wood supply chain in western Paraná so that it is possible to achieve fair economic exploitation through the conscious use of this natural resource, which, despite being abundant in volume, is known to be a finite resource of great importance to humanity. In this context, the study consists of a qualitative survey of representatives of companies operating in the timber supply chain located in the west of Paraná, which sought to identify the sustainability practices that this sector has already adopted. The methodological process used in this study is characterized by a case study that sought to investigate which practices have been employed by this sector to guarantee sustainability. In addition, the study used semi-structured interviews and questionnaires to validate the results based on what was found in the literature. The results made it possible to identify the practices already adopted by supply chain members, emphasizing production based on process efficiency in the face of sustainable economic activity. In addition, the main existing challenges in the sector were verified, as well as being able to present the main challenges involved in the timber activity characterized in the western region of Paraná.